Activation of 5-HT2C receptors in the dorsal periaqueductal gray increases antinociception in mice exposed to the elevated plus-maze - Baptista, Daniela [UNESP]; Nunes-de-Souza, Ricardo Luiz [UNESP]; Canto-de-Souza, Azair [UNESP] (Elsevier B.V., 2012)
Several findings have pointed to the role of the dorsal periaqueductal gray (dPAG) serotonin 5-HT1A and 5-HT2(A-C) receptor subtypes in the modulation of defensive behavior in animals exposed to the elevated plus-maze (EPM). Besides displaying anxiety-like behavior, rodents also exhibit antinociception in the EPM. This study investigated the effects of intra-dPAG injections of 5-HT1A and 5-HT2B/2C receptor ligands on EPM-induced antinociception in mice. Male Swiss mice received 0.1 mu l intra-dPAG injections of vehicle, 5.6 and 10 nmol of 8-OHDPAT, a 5-HT1A receptor agonist (Experiment 1), or 0.01, 0.03 and 0.1 nmol of mCPP, a 5-HT2B/2C receptor agonist (Experiment 2). Five minutes later, each mouse received an intraperitoneal injection of 0.6% acetic acid (0.1 ml/10 g body weight; nociceptive stimulus) and was individually confined in the open (OA) or enclosed (EA) arms of the EPM for 5 min, during which the number of abdominal writhes induced by the acetic acid was recorded. While intra-dPAG injection of 8-OHDPAT did not change open-arm antinociception (OAR). mCPP (0.01 nmol) enhanced it. Combined injections of ketanserin (10 nmol/0.1 mu l), a 5-HT2A/2C receptor antagonist, and 0.01 nmol of mCPP (Experiment 3), selectively and completely blocked the OAR enhancement induced by mCPP. Although intra-dPAG injection of mCPP (0.01 nmol) also produced antinociception in EA-confined mice (Experiment 2), this effect was not confirmed in Experiment 3. Moreover, no other compound changed the nociceptive response in EA-confined animals. These results suggest that the 5-HT2C receptors located within the PAG play a role in this type of environmentally induced pain inhibition in mice. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Antinociception; Elevated plus-maze; Periaqueductal gray matter; 5-HT1A and 5-HT2C receptors; Mice